(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Libraries like every other profession has been obstructed by technological innovations like Integrated Library Management Software (ILMS). ILMS offers numerous benefits and serves as a powerful tool for libraries to efficiently manage their resources, operations and services. Koha as an example of open-source integrated library management software has gained popularity among academic libraries all over the world, Nigeria not left behind. However, with the numerous advantages, low or partial automation was found, of which several studies have been done to delineate the reasons. The study, adopting descriptive survey research design, investigated organizational factors as predictor for motivation to use Koha Integrated Library Management Software in Southwest Universities, Nigeria. The population for this study consists of all the three hundred and eight (308) librarians from all the 22 libraries of universities in Southwest Nigeria that use Koha library management software. From the study population, 175 were sampled using Krejce and Morgan sampling table with an approximate 70% response rate. The study found that organizational factors have significant influence on motivation to use Koha ILMS (Adj. R2 = 0. 254, F(1,118) = 41.429, p = 0.000). The study concluded that Koha ILMS is compatible with library operations. Therefore, the study suggests that both library management and the university management should ensure adequate availability of infrastructures that allow for effective utilization of library oriented technological innovations like ILMS. Keywords: , , ,